ANALISIS JAWABAN SISWA TK TERHADAP PEMBELAJARAN KREATIF - Kusmiyati kusmiyati; Rukmini Rukmini (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
The main issues of this study are how the answers of kindergarten school students to creative learning. The purpose of this study was to analyze the answers of kindergarten school students to the questions that teachers give when learning in the classroom. The research method used is descriptive quantitative research method. The sample of this research is 36 students of Al-Hidayah kindergarten. The results showed that the answers of kindergarten school students Al-Hidayah show the answers creatively in science learning. Kindergarten school teachers can use two types of questions to students, closed or open questions depending on the intent and purpose of the question given.